A new species of suckermouth catfish (Mochokidae: Chiloglanis) from the Rio Mongo in Equatorial Guinea - Schmidt, Ray C.; Barrientos, Christian (Zootaxa, 2019)
A recent expedition surveyed freshwater fishes throughout the continental portion of Equatorial Guinea (Rio Muni). This portion of the Lower Guinean ichthyoprovince is relatively unknown with very few collections occurring since the 1960s. Sampling in the Rio Mongo, a tributary to the Rio Wele, yielded two Chiloglanis species; one putatively ascribed to the widespread species C. cameronensis, and the other species having similarities with C. harbinger described from the Lokoundje River in Cameroon. Morphometric analyses between the specimens from Rio Mongo and paratypes of C. harbinger confirm that they are distinct species and should be described as such. Here we describe Chiloglanis mongoensis sp. nov., a narrow endemic species only known from one locality in the Rio Mongo. We provide measurements from paratypes of C. harbinger and emphasize the need for further expeditions in the area.